PEMBERDAYAAN MASYARAKAT DALAM PROSES PENGEMBANGAN EKOWISATA TAMAN SARI BUWANA DI DESA TUNJUK, KECAMATAN TABANAN, KABUPATEN TABANAN, BALI - Ni Wayan Sri Agustini; I Made Adikampana (JURNAL DESTINASI PARIWISATA, 2014)
ABSTRACT Ecotourism is a trend in the world of tourism in which there is an attempt to empower the community to improve the local economy. Taman Sari Buwana is an ecotourism located in Tunjuk Village, Tabanan District, Tabanan Bali. This study aims to assess the form of community empowerment in the tourism development process, Taman Sari Buwana using qualitative data types with primary and secondary data sources. The Data were collected through observation, library research and in-depth interviews using a Porposive Sampling technique. Taman Sari Buwana is an ecotourism located at Tunjuk Village, Tabanan District, Tabanan Bali. Ecotourism was pioneered by I Ketut Buwana SE.MM born at Banjar Beng Kaja, Tunjuk village. Ecotourism of Taman Sari Buwana is offering alternative tourism activities such as trekking to utilize the resources and culture of Banjar Beng Kaja, Tunjuk Village. This study was conducted to review the form of community empowerment in the tourism development process Taman Sari Buwana. In its development, ecotourism of Taman Sari Buwana empower local communities in three stages: first, the planning of which empowerment in tourism potential mapping, land supply, the provision of facilities and socialization programs. Second, the implementation stage, of which in the implementation of community development and management of ecotourism program. And third, monitoring or evaluation stage including community empowerment in monitoring and benefits of ecotourism  Taman Sari Buwana.